Digital health capacity and pediatric care quality in LMICs: A large-scale analysis of 5311 health facilities - Dan Wang; Zhongliang Zhou; Mengyao Li; Wenhua Wang (Digital Health)
Objective Digital health technologies are crucial for achieving universal health coverage (UHC), especially in low- and middle-income countries (LMICs) with limited digital infrastructure. This study aimed to assess digital health capacity across multiple LMICs and evaluate its association with evidence-based practice (EBP) and patient-centered care (PCC). Methods We analyzed Service Provision Assessment data collected over the past decade, spanning 5311 facilities and 20,880 pediatric visits across eight LMICs. Digital health capacity was measured using the WHO Classification of Digital Health Interventions (CDHI) across five domains: digital infrastructure, client engagement, healthcare providers, data services, and health system managers. EBP was assessed via ten binary items, while PCC was derived from eleven exit interview items using exploratory factor analysis. Multilevel regression models explored relationships between digital health capacity and both EBP and PCC. Results Overall digital health capacity was low (mean = 0.35), with notably low scores for digital infrastructure (0.02), healthcare providers (0.21), and health system managers (0.06). Digital health capacity was significantly associated with improved EBP (Coef. = 0.146, p < 0.001), particularly through digital infrastructure (Coef. = 0.183, p = 0.029), client engagement (Coef. = 0.205, p < 0.001), and provider capacity (Coef. = 0.142, p < 0.001). No significant effect emerged for PCC (Coef.=−0.013, p = 0.531). Conclusions The level of digital health technology in LMICs is generally insufficient, particularly in terms of digital infrastructure, healthcare provider training and health system managers. Although the implementation of digital health technologies has the potential to improve the EBP, its effect on enhancing PCC is relatively limited.